MiR-409-5p as a Regulator of Neurite Growth Is Down Regulated in APP/PS1 Murine Model of Alzheimer’s Disease - Guo, Jing; Cai, Yifei; Ye, Xiaoyang; Ma, Nana; Wang, Yuan; Yu, Bo; Wan, Jun (Frontiers in Neuroscience, 2019)
Alzheimer’s disease (AD) is a heterogeneous neurodegenerative disease. Recent studies suggest that miRNAs expression changes are associated with the development of AD. Our previous study showed that the expression level of miR-409-5p was stably down-regulated in the early stage of APP/PS1 double transgenic mice model of AD. We now report that miR-409-5p impairs neurite outgrowth, decreases neuronal viability and accelerates the progression of Aβ1-42-induced pathologies. In this study, we found that Aβ1-42 peptide significantly decreased the expression of miR-409-5p, which was consistent with the expression profile of miR-409-5p in the APP/PS1 mice cortexes. PLEK was confirmed to be a potential regulatory target of miR-409-5p by luciferase assay and Western blotting. Overexpression of miR-409-5p has an obvious neurotoxicity in neuronal cell viability and differentiation, whereas PLEK overexpression could partially rescue neurite outgrowth from this toxicity. Some cytoskeleton regulatory proteins have been found to be related to AD pathogenesis. Our data show some clues that cytoskeletal reorganization may play roles in AD pathology. The early down-regulation of miR-409-5p in AD progression might be a self-protective reaction to alleviate the synaptic damage induced by Aβ, which may be used as a potential early biomarker of AD.